Effect and mechanism of synergistic enhancement of gas displacement in coal by micro-nano bubbles and surfactants - Yong CHEN; Pengfei WANG; Ronghua LIU; Kaixin LIU; Gaogao WU; Xinzhe WANG (Meitan xuebao)
In order to achieve drag reduction, permeability enhancement and enhanced displacement of coal gas, the liquid-gas coupling medium was obtained based on the coexistence characteristics of micro-nano bubbles, surfactants and water medium. The synergistic effect of the liquid-gas coupling was characterized by the flow rate of the loop and the rotational viscosity. The synergistic effect of micro-nano bubbles and surfactants was quantified based on the instantaneous flow rate of seepage and gas permeability measurement. The displacement mechanism under the synergistic effect of micro-nano bubbles and surfactants was revealed through Darcy seepage. The results show that after the synergistic effect of micro-nano bubbles and surfactants when the axial pressure/confining pressure is 3 and 5 MPa, the instantaneous flow rate of anthracite increases by 1.61 and 2.44 times and the gas permeability increases by 1.61 and 2.39 times respectively compared with distilled water，the instantaneous flow rate of long flame coal increased by 1.43 and 1.67 times and the gas permeability increased by 1.44 and 1.68 times respectively compared with the medium containing surfactant, the instantaneous flow rate of anthracite increased by 1.08 and 1.21 times and the gas permeability increased by 1.08 and 1.13 times respectively, the instantaneous flow rate of long flame coal increased by 1.07 and 1.11 times and the gas permeability increased by 1.08 and 1.11 times respectively. When the coal with the same metamorphic degree is displaced by distilled water medium, surfactant containing medium and liquid gas coupling medium, the instantaneous flow rate and gas permeability increase gradually, and the long flame coal shows a more obvious enhancement effect than anthracite coal. With the increase of axial pressure/confining pressure, the displacement intensity of different media decreased to a certain extent. However, the synergistic effect of micro and nano bubbles and surfactants shows that under the same load condition, the seepage strength of liquid gas coupling medium is greater than that of distilled water medium and surfactant containing medium and the seepage difference between different axial pressure/confining pressure is significantly reduced. The synergistic effect of micro-nano bubbles and surfactant derived drag reduction performance and boundary slip which provided the driving force for gas seepage displacement. Based on the characteristics of pore seepage and boundary slip, the resistance reduction seepage model was established by comparing the internal pore structure of coal with that of circular pipe pores. Based on Darcy seepage, the characteristics and mechanism of the interface of liquid gas coupling medium on coal water injection seepage displacement were characterized. The synergistic effect of micro nano bubble surfactant liquid gas coupling has put forward a new technical direction for coal seam water injection seepage displacement and enhanced permeability drainage.